Evaluating the sustainability of the physical urban form of Sanandaj City, Iran [electronic resource] - Farzin Charehjoo, 1980- (2013)
Thesis (Ph.D (Perancangan Bandar dan Willayah)) - Universiti Teknologi Malaysia, 2013